Semantic features of negative constructions in scientific monologue and scientific dialogue on the material of Russian and English languages - Belikova, Katsiaryna A. (Journal of the Belarusian State University. Philology, 2023)
Semantic peculiarities of the use of negative constructions that denote the absence of action, phenomenon or property in scientific speech are demonstrated. The analysis is based on the material of Russian and English languages. Quantitative and qualitative differences of usage of the negative indicators with lexical-semantic groups of verbs in scientific monologue and scientific dialogue are revealed. It is established that the semantic differences of the negative constructions in scientific monologue and scientific dialogue are determined by the specific pragmatic tasks that are solved by the author or speaker.
Keywords: negative constructions; scientific discourse; scientific monologue; scientific dialogue; semantic features